VARIOUS POLICIES OF THE JAPANESE OCCUPATION GOVERNMENT AGAINST ETHNIC IN MALAYA IN 1942-1945 - Hasti Sulaiman (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
This study aims to describe the initial arrival of Chinese and Indians in Malaya, the Japanese invasion and occupation of Malaya and the policies implemented by the Japanese occupation government in Malaya. This study uses the method of literature (library research). The research results show that the beginning of the arrival of the Chinese in Malaya was estimated from the beginning of the seventh century, the Chinese came to establish trade relations with the Malays, they bartered their natural products. China's natural products include silk, salt, rice, and earthen tools. Similar to the Chinese in Malaya, the arrival of India in Malaya long before the arrival of the Japanese. Ancient India also exerted great influence in Southeast Asia through trading links, religious missions, wars and other forms of contact. Indian traders had traveled this region including the southern tip of the Southeast Asian peninsula with maritime trade. The initial Japanese policy towards China in Malaya was very cruel, and showed extraordinary suspicion towards the Chinese in Malaya. Many Chinese in Malaya participated in anti-Japanese activities before the invasion. Before launching the invasion, the Japanese treated the Malays well. Japan's policy towards Malays is to provide several privileges compared to China. Likewise with the Indians, they also enjoyed better treatment during the Japanese occupation of Malaya than the Chinese. This happened to encourage Indian national activities aimed at overthrowing British rule in India, Japan supporting organizations such as the Indian Independent League (IIL / Indian Independence League).